Light Induced Properties of Chalcones Correlated with Molecular Structure and Photophysical Properties for Permanent Optical Storage Device - Hegde, Gurumurthy; M. M., Yusoff; Sidharth, S. N.; Yuvaraj, A. R.; Hui, Tai Joo; Sarojini, B. K. (Trans Tech Publications, Switzerland, 2014)
The photoisomerization effect on new chalcone derivative is reported. The synthesized chalcone was characterized by different spectral analysis such as 1 H-NMR, 13C-NMR, FTIR, LCMS and UV/Vis. It revealed the photoisomerization effect in solution, the EZ isomerization occurred around 60sec, whereas ZE isomerism occurred at 0min. This chalcone derivative is more useful in fabrication of permanent optical storage devices.